Properties of mortar according to substitution rate of ferro-nickel slag powder - Jeong, Hyunsu; Jeon, Eunyeong; Lee, Jeongtaek; Lee, Sangsoo (Edelweiss Applied Science and Technology, 2024)
This study analyzes the properties of cement mortar according to the substitution of fine ferro-nickel slag powder in various types of fine aggregate, with the aim of recycling industrial waste. When using a ferro-nickel slag powder as the admixture of cement mortar, it is determined that substitution rates of 30% and higher are unsuitable for use as mortar. In order to solve this problem, it is believed that it is necessary to explore means to improve the initial strength degradation that results when fine ferro-nickel slag powder is mixed. Furthermore, the differences in carbon dioxide reduction according to fine ferro-nickel slag powder substitution rates were found to be minimal, and it is thought that additional performance analysis is necessary.